Ardent spirits leaving home, coming back - Price, Reynolds 1933-2011 (Scribner, 2009)
Recounts the author's observations of post-World War II Great Britain, his Oxford University education, and his encounters with such figures as J.R.R. Tolkien, W.H. Auden, and Stephen Spender.
Keywords: Price, Reynolds -- 1933-; Price, Reynolds -- 1933-2011; University of Oxford -- Students -- Biography; Duke University -- Faculty -- Biography; Geschichte 1900-2000; Authors, American -- 20th century -- Biography; English teachers -- United States -- Biography; USA; Autobiografie -- 1955-1961